DELINEATION OF SUBSURFACE STRUCTURES OF SEMANGGOL FORMATION, NORTH PERAK USING MAGNETIC DATA - Chian, O.W. (GEOMATE International Society, 2019)
The Semanggol Formation has been studied widely and published by many, but only focus on areas of northern and southeast Kedah. Limited data have been studied and published on Perak area, especially Gunung Semanggol. The research is aimed to augment the presently limited knowledge on the hill, particularly the subsurface structure. In addition, new lithology such as a breccia formation with tens of meters width of what appears to be a breccia granitic matrix was identified in an abandoned quarry. Therefore, a study on the application of geophysical methods covering the Semanggol Formation located at Semanggol area has been carried out. The main aim of this study was to conduct a magnetic survey to study the subsurface and possibility of granitic bodies in Gunung Semanggol. The total magnetic field data were obtained by using a proton free-precision magnetometer, recording the total ground magnetic field along the transverse. There was a total of 184 magnetic stations established during the survey with a 500 m to 1 km spacing. Data reduction was processed using Oasis Montaj software to produce Total Magnetic Intensity (TMI), Reduction to Pole (RTE), Regional Anomaly and Residual Anomaly maps for qualitative interpretation. The interpreted field data gave the results of total component measurements of magnetic anomaly varying between minimum negative value around 180 nanoTesla (nT) and maximum around 510 nanoTesla (nT) as shown in TMI map. Besides, the regional magnetic map shows a gradual decrement of magnetic intensity towards east and southeast. And residual magnetic map reveals that the dominant orientation for magnetic lineaments in the NE-SW direction. However, geochemical tests have to be conducted to study the possibility of granitic bodies. Â© 2019. Int. J. of GEOMATE. All rights reserved, including the making of copies unless permission is obtained from the copyright proprietors.